2020
DOI: 10.1038/s41580-020-0272-6
|View full text |Cite
|
Sign up to set email alerts
|

The nucleolus as a multiphase liquid condensate

Abstract: Among numerous microscopically visible nuclear substructures, the nucleolus is the most prominent and represents a functionally and biophysically distinct body or compartment. The nucleolus is, in fact, so prominent that it drew the attention of early biologists over 200 years ago, in light microscopy studies by Fontana, Valentin and Wagner 1. Following these early descriptions came the understanding of the functional importance of the nucleolus, including its primary role as the site for the initial steps of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
592
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 700 publications
(695 citation statements)
references
References 117 publications
(135 reference statements)
10
592
0
1
Order By: Relevance
“…Gelation is related to liquid–liquid phase separation (LLPS), a fundamental physical phenomenon describing a density transition of an initially homogenous solution into a dense and a dilute liquid phase that can stably coexist. This phenomenon underlies many biological processes including the formation of membraneless compartments (reviewed in ( 183 )), notably RNA-containing subcellular entities (called RNA granules) such as the nucleolus in the nucleus ( 184 ) and SGs in the cytoplasm ( 181 ).…”
Section: Rna G-quadruplexes In Biomolecular Condensates and Their Conmentioning
confidence: 99%
“…Gelation is related to liquid–liquid phase separation (LLPS), a fundamental physical phenomenon describing a density transition of an initially homogenous solution into a dense and a dilute liquid phase that can stably coexist. This phenomenon underlies many biological processes including the formation of membraneless compartments (reviewed in ( 183 )), notably RNA-containing subcellular entities (called RNA granules) such as the nucleolus in the nucleus ( 184 ) and SGs in the cytoplasm ( 181 ).…”
Section: Rna G-quadruplexes In Biomolecular Condensates and Their Conmentioning
confidence: 99%
“…Some of these biomolecular condensates are constitutive in eukaryotic cells (1), while others only occur in specific cell types or in response to certain environmental stimuli (2–8). While a condensate may contain hundreds of different components (4), its composition is typically dominated by a small number of major constituents that define the condensate identity and likely control its overall biochemical and biophysical properties (1, 2, 5, 9). These high abundance constituents can be thought of as the basis of the condensate’s unique internal solvent environment, into which other (solute) biomolecules may be partitioned.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, extensive studies on the properties of non-membrane-bound compartments in the cellular cytoplasm have shown that concepts in phase separation drawn from physical chemistry can describe their formation and behaviour [1][2][3][4] . Current evidence also suggests that phase separation plays a role in the organization inside the cell nucleus [5][6][7][8] . However, the influence and role of DNA on the physical chemistry of phase separation is not well understood.…”
mentioning
confidence: 99%